IMPLEMENTASI PERDA NOMOR 08 TAHUN 2012 TENTANG RETRIBUSI JASA USAHA DI KABUPATEN KAMPAR (Studi Kasus Retribusi Usaha Perkebunan Bersubsidi Di Kecamatan Kampar) - DWI YANTI UTARI; FEBRI YULIANI (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
ABSTRACT : PERDA IMPLEMENTATION OF THE NUMBER 08 IN 2012 IN THEDISTRICT BUSINESS SERVICES LEVY KAMPAR (Levy Case Study PlantationSubsidized In the District of Kampar)The Governance of autonomy is a very precise answer in driving the process ofimplementation of the Government and democratic development. With the granting ofregional autonomy granted by the Central Government to a region that all aim to promote andeducate the general welfare of the Nation, the Government needs to implement the division oftasks, so that the country can be achieved objectives in an optimal way that is efficient andeffective. One of the government programs in the Kampar district is especially plantationprogram subsidized distribution of oil palm seedlings to the community. In carrying out theprogram of subsidized distribution of oil palm seedlings set in Regulation No.. 08 Year 2012on service levies Plantation, Plantation Office under the authority of Kampar district.With the passage of the function and role of the Estates Department officials to create orderand clarity to the people who are in their environment. What is the procedure of withdrawaland levy payments and subsidized the purchase of oil palm seedlings , in Regulation No. 08of 2012 levy is included into the Levy Production Sales Daerah.Namun there are severaldeterminants implementation of the Implementation Regulation No. 08 of 2012 by EdwardIII , namely : communication is the delivery of from policy making to the implementingagency policies and service levies Plantation consistent information delivered , is crucialcommunication success in achieving the goal of implementation is the availability ofresources to implement a Resource policy is one factor that should always be considered .Resources mentioned is sufficient staff , information , authority and facilities that support theimplementation of the course of collection service levies Plantation in Kampar district .Attitude/position that is related to the implementation of the decision showed a positiveattitude towards the decision / policy and know what they are doing and have the capacityand made them commit berkonsisten in running and not doing discriminative policies againstsociety. Bureaucratic structure is in this case concerning the ability of structures to enable thepolicies that have been made and suggests cooperation of many people and is on the run inaccordance with the normative values contained in the policy.Keywords: Implementation, Public Policy, Retribution